Pengembangan Aplikasi Penjemputan dan Pengantaran Penumpang Travel berbasis Android (Studi Kasus Ladju Travel Malang) - Gusti Agung Suastika Adinata; Agi Putra Kharisma; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Travel services is one of services that people need to travel and now many companies have open travel services. But problems arise for passengers and Ladju Travel, namely passengers who do not know the location of the travel car. In addition, another problem is the way Ladju Travel in resolving the Traveling Salesman Problem problem is still using manual methods so that the order of pickup and delivery is not good. To solve this problem, an Android-based travel passenger pickup and delivery application was developed. This application is divided into three, there are applications for drivers, passengers and management. Application development use the Waterfall model and for requirement modeling and design use the Unified Modeling Language. Traveling Salesman Problem using Greedy algorithms. Applications was tested using Black Box Testing and Usability Testing. Black Box Testing will also be perform on Compatibility Testing. Black Box Testing carried out on all functional requirements produces valid status for all functional on three different Android versions, namely version 5.0-5.1 (Lollipop), 6.0 (Marshmellow), and 7.0-7.1 (Nougat). The result of Usability Testing that use the System Usability Scale questionnaire is 78.75 score for the application for passengers, 69 score for the application for the driver and 70 score for the application for management. These results are above the minimum average score of 68.